Properties and characteristics of nanocrystalline cellulose isolated from olive fiber. (1st August 2020) - Kian, L.K.; Saba, N.; Jawaid, M.; Alothman, O.Y.; Fouad, H.
Highlights: Olive fiber as alternative biomaterial for nanocrystalline cellulose extraction. Isolation of individual nanoparticles with well dispersed behaviour. Enhanced cellulose compartment within nanocrystals feature. Highly strong and rigid structure of produced nanocrystalline cellulose. Improved thermal stability with different acid hydrolysis reaction times treatment. Abstract: Olive fiber is a sustainable material as well as alternative biomass for extraction of nanocrystalline cellulose (NCC), which has been widely applied in various industries. In the present study, ONC-I, ONC-II, and ONC-III were extracted from olive stem fiber at different hydrolysis reaction times of 30 min, 45 min, and 60 min, respectively. The nanoparticle size was found gradually reducing from ONC-I (11.35 nm width, 168.28 nm length) to ONC-III (6.92 nm width, 124.16 nm length) due to the disintegration of cellulose fibrils. ONC-II and ONC-III possessed highly pure cellulose compartments and enhanced crystals structure. This study also showed that rigidity increased from ONC-I to ONC-II. ONC-III showed the highest crystallinity of 83.1 %, endowing it as a potentially reliable load-bearing agent. Moreover, ONC-III exhibited highest stable heat resistance among the chemically-isolated nanocellulose. We concluded that olive NCC could be promising materials for a variety of industrial applications in various fields.